Causes and Solutions for Pending Cases of Outpatient Claims at RS X Bukittinggi - Yastori (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Pending claims have an impact on the delay in payment of medical services which has an impact on the performance of hospital employees, thus affecting the quality of hospital services. The purpose of this study was to determine the causes and solutions to pending cases of outpatient claims at X Bukittinggi Hospital. The study was conducted in February-September 2023 in the Casemix and medical records unit. The population of this study was 2,627 pending claim cases in 2023. The sample in the study used the Slovin formula, obtaining a sample of 91 pending outpatient claim documents. The research design is a qualitative study of outpatient pending claim document review and in-depth interviews. The causing pending claims for inpatient care consisted of errors in the coding process by the coder and the coding input process by the grouper, errors in placing primary and secondary diagnoses on the medical resume, unclear writing on the CPPT, incomplete medical resume, confirmation of supporting evidence in establishing the primary and secondary diagnoses, evidence of supporting examinations, confirmation of diagnosis establishment for exceptional cases that occur because there are indications determined by the doctor after the results of further examinations, regulations in determining the category of treatment class, compliance with related regulations. Pending claim solutions include understanding BPJS claim regulations and related regulations that regulate things like codification rules and rules related to completeness of documents.